Fungal Diversity in the Neptune Forest: Comparison of the Mycobiota of Posidonia oceanica, Flabellia petiolata, and Padina pavonica - Poli, Anna; Bovio, Elena; Ranieri, Lucrezia; Varese, Giovanna Cristina; Prigione, Valeria (Frontiers in Microbiology, 2020)
Fungi are widely distributed in the Oceans, interact with other organisms and play roles that range from pathogenic to mutualistic. The present work focuses on the characterization of the cultivable mycobiota associated with the seagrass Posidonia oceanica (L.) Delile collected off the Elba Island (Italy). We identified 102 taxa (mainly Ascomycota) by the mean of a polyphasic approach. Leaves, rhizomes, roots and matte were characterized by unique mycobiota revealing a “plant-part-specificity”. The comparison with the mycobiota associated with the green alga Flabellia petiolata and the brown alga Padina pavonica underlined a "substrate specificity". Indeed, despite being part of the same phytocoenosis, these photosynthetic organisms recruit different fungal communities. The mycobiota seems to be necessary for the host’s defense and protection, playing, in this way, remarkable ecological roles. Among the 61 species detected in association with P. oceanica (including two species belonging to the newly introduced genus Paralulworthia), 37 were reported for the first time from the Mediterranean Sea Keywords: Marine Fungi; Mediterranean Sea; Seagrass; Algae; Phylogeny; Lulworthiales